An orally delivered bacteria‐based coacervate antidote for alcohol detoxification. (May 2023) - Qiao, Ji-Yan; Li, Wen; Zeng, Run-Yao; Yu, Yun-Jian; Chen, Qi-Wen; Liu, Xin-Hua; Cheng, Si-Xue; Zhang, Xian-Zheng
Abstract: Alcohol intoxication causes serious diseases, whereas current treatments are mostly supportive and unable to convert alcohol into nontoxic products in the digestive tract. To address this issue, an oral intestinal-coating coacervate antidote containing acetic acid bacteria (AAB) and sodium alginate (SA) mixture was constructed. After oral administration, SA reduces absorption of ethanol and promotes the proliferation of AAB, and AAB converts ethanol to acetic acid or carbon dioxide and water by two sequential catalytic reactions in the presence of membrane-bound alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH). In vivo study shows that the bacteria‐based coacervate antidote can significantly reduce the blood alcohol concentration (BAC) and effectively alleviates alcoholic liver injury in mice. Given the convenience and effectiveness of oral administration, AAB/SA can be used as a promising candidate antidote for relieving alcohol-induced acute liver injury. Graphical abstract: An orally delivered bacteria‐based coacervate antidote can convert ethanol to acetic acid or carbon dioxide and water by two sequential catalytic reactions of membrane-bound alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) in the gastrointestinal tract for relieving alcohol-induced acute liver injury. Image 1